Ergonomi Terintegrasi dan Kesehatan Mental Kerja: Peningkatan Kesadaran Pekerja PT. XYZ di Era Digital - Rizkiyah, Naila; Nurrohman, Rosyid (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The rapid development of the digital era has led to a major shift in the modern workplace, with over 1.5 billion people spending more than six hours daily in front of computer screens. This working condition poses significant occupational health risks, including Musculoskeletal Disorders (MSDs) such as Low Back Pain (LBP) and neck strain, with a global prevalence of 60-80%. Furthermore, prolonged screen exposure and high workload contribute to mental health issues like chronic stress and digital fatigue. This community service aimed to increase awareness among PT. XYZ employees regarding the importance of integrated ergonomics to achieve optimal productivity. The method used was an informative sharing session through a presentation and discussion. The material emphasized a three-pronged intervention approach: physical ergonomics (workstation adjustment), technology-based interventions (wearable devices, break reminder apps, and electromagnetic radiation prevention), and mental well-being integration (mindfulness and relaxation techniques). The results showed a significant increase in participant understanding of the health risks and the practical steps to implement integrated ergonomic solutions. It was found that combining technology-based reminders and mindfulness exercises can reduce health complaints by up to 40% better than physical interventions alone. The implication of this service is the recommendation for PT. XYZ to adopt an integrated ergonomic policy that addresses physical, technological, and mental aspects to create a healthier, safer, and more productive work environment for its employees.